Herpes zóster Simuladores que pueden desviar nuestra atención - Gisela Vaglio Giors; David Aldo De Luca; María Eugenia Echeverría; María Carolina Baztán Piñero; Ana Clara Torre; Ricardo Luis Galimberti (Revista del Hospital Italiano de Buenos Aires)
-